Refractory mucocutaneous leishmaniasis resolved with combination treatment based on intravenous pentamidine, oral azole, aerosolized liposomal amphotericin B, and intralesional meglumine antimoniate. (August 2020) - Basile, Gregorio; Cristofaro, Glauco; Locatello, Luca Giovanni; Vellere, Iacopo; Piccica, Matteo; Bresci, Silvia; Maggiore, Giandomenico; Gallo, Oreste; Novelli, Andrea; Di Muccio, Trentina; Gramiccia, Marina; Gradoni, Luigi; et al.
Highlights: Comorbidities limit treatment options in tegumentary leishmaniasis. Combination therapy should be considered in relapsing mucocutaneous leishmaniasis. We report the use of aerosolized liposomal amphotericin B as add-on treatment for refractory mucosal lesions. Abstract: Introduction: Mucocutaneous leishmaniasis (MCL) is a complication of tegumentary leishmaniasis, causing potentially life-threatening lesions in the ear, nose, and throat (ENT) region, and most commonly due to Leishmania (Viannia) braziliensis . We report a case of relapsing MCL in an Italian traveler returning from Argentina. Case description: A 65-year-old Italian male patient with chronic kidney disease, arterial hypertension, prostatic hypertrophy, and type-2 diabetes mellitus was referred for severe relapsing MCL acquired in Argentina. ENT examination showed severe diffuse pharyngolaryngeal edema and erythema, partially obstructing the airways. A nasopharyngeal biopsy revealed a lymphoplasmacytic inflammation and presence of Leishmania amastigotes, subsequently identified as L. (V.) braziliensis by hsp70 PCR-RFLP analysis and sequencing. Despite receiving four courses of liposomal amphotericine B (L-AmB) and two courses of miltefosine over a 2-year period, the patient presented recurrence of symptoms a few months after the end of each course. After the patient was referred to us, a combined treatment was started with intravenous pentamidine 4 mg/kg on alternate days for 10 doses, followed by one dose per week for an additional seven doses, intralesional meglumine antimoniate on the nasal lesion once per week for six doses, oral azoles for three months, and aerosolized L-AmB on alternate days for three months. The treatment led to regression of mucosal lesions and respiratory symptoms. Renal function temporarily worsened, and the addition of insulin was required to maintain glycemic compensation after pentamidine discontinuation. Conclusions: This case highlights the difficulties in managing a life-threatening refractory case of MCL in an Italian traveler with multiple comorbidities. Even though parenteral antimonial derivatives are traditionally considered the treatment of choice for MCL, they are relatively contraindicated in cases of chronic kidney disease.The required dose adjustment in cases of impaired renal function is unknown, therefore the use of alternative drugs is recommended. This case was resolved with combination treatment, including aerosolized L-AmB, which had never been used before for MCL.